Impact Of Clinical Pharmacist Intervention By Using Digital Technology On Clinical Outcomes Among Pregnant Women: Rationality Of Drug Prescriptions At A Tertiary Hospital In Kelantan - Al-Shakhshir, Sami M. (2019)
Pregnant women need unique pharmaceutical and medical care to avoid any harmful and birth defects. Three main objectives were assessed in this study which were measuring the impact of an educational program using WhatsApp on pregnant women knowledge, perceptions, practice, drug adherence, health literacy, and diabetic and/or hypertensive participants’ clinical outcomes as well as measuring healthcare professionals’ knowledge, practice, and teratogenicity risk perceptions towards medications used during pregnancy. The last aim was to evaluate the rational drugs’ prescribing pattern at the gynecology department using WHO/INRUD drug prescribing indicators. Methodology: Three methodologies were used in this study. A randomized control trial was used in assessing the impact of an educational program on pregnant women. Where 800 patients were randomly divided into intervention and control groups. By using WhatsApp application, an educational program was sent to all participants whereas a tailored educational program was sent only to pregnant patients with diabetes and/or hypertension. All study domains were measured using a pre-validated questionnaire and data collection sheet before, after and at one month after the end of the education. A pre-validated questionnaire was distributed to all healthcare providers and pharmacists at the gynecology department to measure their knowledge, perceptions, and teratogenicity risk perceptions towards medications use during pregnancy. Finally, a total of 741 prescriptions were randomly selected from patients’ medical files and analyzed using WHO/INRUD drug prescribing indicators. Appropriate data analysis was made using SPSS version 22.